Evaluation of the Haemoglobin Colour Scale and comparison with the HemoCue haemoglobin assay - Paddle J.J (The World Health Organization, 2002)
OBJECTIVE: To evaluate the Haemoglobin Colour Scale developed by WHO for estimating haemoglobin concentration and to compare the results obtained using it and the HemoCue assay with those determined using a reference method, the Technicon H3 analyser. METHODS: The Colour Scale and HemoCue assay were used to test 408 blood samples. Subsequently, Bland-Altman plots were determined and the proximity of the test results to those obtained using the reference method was determined. FINDINGS: The mean difference between the Haemoglobin Colour Scale and the reference method was 0.19 g/dl (95% confidence interval: 3.50 g/dl below to 3.11 g/dl above); the corresponding value for the HemoCue assay was 0.50 g/dl (1.16 g/dl below to 0.16 g/dl above). Only 46.08% of the results obtained by means of the Colour Scale were within 1.0 g/dl of the reference method, whereas 95.34% of the HemoCue results fell within this limit; 22.79% of the Colour Scale results but none of the HemoCue results lay more than 2.0 g/dl from the reference method. CONCLUSION: The Haemoglobin Colour Scale test is too inaccurate for general use, particularly if devices such as the HemoCue are available.